Penerapan Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) Untuk Meningkatkan Hasil Belajar Siswa Kelas VIII Pada Materi Sumber Daya Alam Negara-Nagara Asean di SMP Negeri 25 Kota Tidore Kepulauan - Farida Maswara; Andi Suaema; Dahri Hi. Halek (Peneliti.net, 2022)
This research was conducted because of the low learning outcomes of students in Social Sciences Geography lessons at SMP Negeri 25 Tidore Islands City. The researcher applies Numbered Heads Together (NHT) cooperative learning in the learning process. It is hoped that this model can improve student learning outcomes on Natural Resources of Asean Countries class VIII SMP Negeri 25 Tidore Islands. This classroom action research was carried out in the odd semester of the 2021/2022 academic year in Class VIII of SMP Negeri 25 City of Tidore Islands. From the results of the study, it was found that the students' learning outcomes for social science geography from 71.42 in the first cycle to 85.71 in the second cycle. Thus, the cooperative learning model of the Numbered Heads Together type can improve the geography social studies learning outcomes of students in class VIII of SMP Negeri 25 Tidore Islands City.